The brave learner : finding everyday magic in homeschool, learning, and life - Bogart, Julie, 1961- (A TarcherPerigee book, 2019)
"A joyful and accessible approach to homeschool that harnesses children's natural curiosity and makes learning a part of everyday life, whether they're in elementary or high school"--